Effectiveness of understanding the post-operative instructions with respect to extraction of teeth in rural population through verbal, written and audio-visual aids. - N, Akshaya; P, Sri Harini; Chandrasekaran, Balamanikandasrinivasan (Bangladesh Journal of Medical Science, 2024)
Aim: To compare the efficacy between verbal, written & audio-visual modes of communication in relation to post-operative instructions after extraction of teeth. Materials & Methods: Ninety patients were equally divided into three groups. Group 1 were given verbal instructions, Group 2 in written format and Group 3- Audio visual mode. Their responses were recorded using a standard questionnaire after 24 hours of extraction and subjected to statistical analysis. Results: Significant differences (p<0.05) was found when the responses were compared between Group 1 and Group 3 and Group 2 and Group 3. Conclusion: Patients who received post-operative instructions through audio-visual mode (Group 3) had more understanding when compared to other groups. Incorporation of technology in communication has to be encouraged as it helps for better understanding. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S48-S52